In vitro activity of Triazolo[1,5-a] pyrimidine carboxylic acid extracted from microalgae Hapalosiphon welweschii againstTrichomonas vaginalis - Khalaf, Amal (University of Thi-Qar Journal of Science, 2019)
The present study targets the protozoan parasite Trichomonas vaginalis that causes a healthy problems among women and rarely among men , by the application of natural product or secondary metabolites extracted from the microalgae Hapalosiphon welweschii for the first time in Iraq . methanol extract was explained high activity in three concentration recording 100% of parasite death at 200 µgof methanol extract in about two days while 150 and 100 µgof extract reports activity against the parasite after three and four days post treatment respectively . GC- Mass spectrum of the methanol extract has explain presence of the compound Triazolo[1,5-a] pyrimidine carboxylic acid in about 13.28 % from the total composition of methanol extract of microalgae H. welweschii .